The Problem Based Learning Method's Consequences for MTs Nahdiyyatul Islamiyah's Fiqh Instruction - Abd. Halim Nasution; Mahidin (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This study examines how PBL (Problem Based Learning) is being implemented in fiqh subjects at MTs Nahdiyatul Islamiyah. It discusses three main points: how PBL is being implemented, what supports and hinders its implementation, and how PBL is having an impact at MTs Nahdiyatul Islamiyah. Teachers of fiqh subjects and MTs Nahdiyatul Islamiyyah students serve as informants in this field study, which employs descriptive qualitative methods.The findings from observations and interviews served as the primary data sources for this study; supporting data came from books, journals, and references that discussed the findings of the investigation. The study's findings demonstrate that the application of PBL in problem-solving is modified according to class level, and that PBL's impact on learning motivation and student accomplishment stems from the process's significance.Because PBL involves solving problems that are consistent with real-world situations, the material is relevant and lends credence to the implementation of problem-based learning in jurisprudence. these days, thus problem solving requires the use of HOTS thinking abilities. The reality that pupils have varying personal capacities is what prevents PBL from being implemented.